Ferroptosis-Related Long Noncoding RNAs as Prognostic Biomarkers for Ovarian Cancer - Wang, Kaili; Mei, Shanshan; Cai, Mengcheng; Zhai, Dongxia; Zhang, Danying; Yu, Jin; Ni, Zhexin; Yu, Chaoqin (Frontiers in Oncology, 2022)
Ovarian cancer (OC) is a highly malignant gynecologic tumor with few treatments and poor prognosis in the current diagnostic markers and effective interventions. Currently, more effective ways of diagnosis and treatment are urgently needed. In spite that the current evidence shows that ferroptosis is implicated in the development and therapeutic responses of various types of tumors, to some extent it is unclear that ferroptosis affects OC. To explore the potentials of ferroptosis-related genes as biomarkers and molecular targets of diagnosing and intervening OC, this study collected several data sets from the Cancer Genome Atlas-OC genes (TCGA-OC), analyzed and identified the co-expression profiles of 60 ferroptosis-related genes and two subtypes of ferroptosis related to OC, and further examined and analyzed the differentially expressed genes of two subtypes. Results indicated that expression levels of ferroptosis genes were significantly correlated with the prognosis of patients with OC. The single-factor Cox and LASSO analysis identified eight of LncRNAs from the screened ferroptosis-related genes, including LncRNA RP11-443B7.3, RP5-1028K7.2, TRAM2-AS1, AC073283.4, RP11-486G15.2, RP11-95H3.1, RP11-958F21.1, and AC006129.1. A significant risk scoring model was constructed between OC and ferroptosis-related LncRNAs, and showed a good performance in the judgment of patient prognosis; in the tumorous risk scores, the high- and low-risk groups presented obvious differences in clinical characteristics, tumor mutation burden, and tumor immune cell infiltration, indicating that the risk score has a good predictive ability for the benefit of immunotherapy and may provide data support for the implementation of precise immunotherapy for OC. In summary, in spite that in vivo tests and researches are needed in the future, our bioinformatics analysis has powerfully supported risk signature of ferroptosis-related LncRNAs for predicting prognosis in OC, which provides a clue that these identified eight of LncRNAs have great potentials of developing as diagnostic markers and intervention molecules for OC.